2018
DOI: 10.1164/rccm.201709-1899oc
|View full text |Cite
|
Sign up to set email alerts
|

Grief Symptoms in Relatives Who Experienced Organ Donation Requests in the ICU

Abstract: Experience of the organ donation process varied between relatives of donor versus nondonor patients, with relatives of nondonors experiencing lower-quality communication, but the decision was not associated with subsequent grief symptoms. Importantly, understanding of brain death is a key element of the organ donation process for relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 36 publications
2
64
0
3
Order By: Relevance
“…Knowing these factors will help ICU teams improve the family's experience. Other studies show a similar prevalence of complicated grief symptoms at 6 months, ranging between 20% and 45% for complicated grief and 26% and 44% for PTSD . These studies show that perceptions of the quality of EOL care are significantly associated with complicated grief and PTSD, such as dissatisfaction with information and communication, unreasonable care, perception that the deceased person had not achieved a sense of completion about his or her life, presence at time of death, or discordance between family members' preferences for decision‐making and their actual decision‐making roles .…”
Section: Grief and Bereavementsupporting
confidence: 51%
See 1 more Smart Citation
“…Knowing these factors will help ICU teams improve the family's experience. Other studies show a similar prevalence of complicated grief symptoms at 6 months, ranging between 20% and 45% for complicated grief and 26% and 44% for PTSD . These studies show that perceptions of the quality of EOL care are significantly associated with complicated grief and PTSD, such as dissatisfaction with information and communication, unreasonable care, perception that the deceased person had not achieved a sense of completion about his or her life, presence at time of death, or discordance between family members' preferences for decision‐making and their actual decision‐making roles .…”
Section: Grief and Bereavementsupporting
confidence: 51%
“…Another important aspect of bereavement research in this context is the very high response rates when using telephone follow up. Indeed, rates vary between 78% and 90% at 1 month, 68% and 87% at 3 months, and 60% and 80% at 6 months . Not only are family members keen to participate for altruistic reasons (help other family members, improve practices), but they also participate because the follow‐up calls are experienced as a form of support, an opportunity to express themselves and to share difficult emotions, as well as a means to not feel abandoned .…”
Section: Research Follow‐up Calls: Combining Research and Supportmentioning
confidence: 99%
“…Interestingly these negative impacts were due to factors that could be improved in the ICU setting. A study assessing grief symptoms [64] in a large number of relatives of brain-dead patients for whom organ donation was discussed in the ICU showed that one month after the patient's death, relatives of non-donors describe a significantly more burdensome experience: they were more dissatisfied with communication, more often shocked by the request and more often found the decision difficult. Interestingly, decisional regret more often occurs when the decision was to decline donation [65] and when organ donation was raised before FMs were informed of the patient's death [66].…”
Section: Impact Of Organ Donation On Post-icu Family Outcomesmentioning
confidence: 99%
“…families to give meaning to the patient's death. Research shows that not understanding brain death is associated with an increased risk of developing complicated grief [64]. A small randomized controlled trial showed that family presence during brain death evaluation improved understanding of brain death with no apparent adverse impact on psychological well-being [67].…”
Section: Quality Of Communication Is Important: Understanding the Caumentioning
confidence: 99%
“…Fulton et al were the first to explore the impact of organ donation on the grieving process and found that solace and comfort were reported by the majority . However, this seminal research and subsequent investigations have largely focused on psychological outcomes in the context of DBD despite implementation of the cDCD pathways of care. Similarly, little is known about the family experiences of cDCD at the time of a sudden bereavement in the ICU.…”
Section: Introductionmentioning
confidence: 99%